The potters of Buur Heybe, Somalia - Belkin, Tara.; Brandt, Steven A.; Noor, Surer (Walnut Creek, Calif. : Left Coast Press, 2006)
In a small village in southern Somalia, only the men make pottery, skillfully coordinating their hands and feet. But, like their ancestors, the women mine the clay. This program reveals the entire process of turning rough soil into beautifully decorated pottery, and describes the role of pottery in the economy of the village.
Documentary.
Editor, Steven Brandt.
Narrator: Surer Noor.
Keywords: Potters -- Somalia -- Buur Heybe; Pottery, African; Pottery, African; Pottery -- Somalia -- Buur Heybe; Somalia -- Social life and customs